Micro-XCT analysis of anatomical features and dimensions of the incisive canal: implications for dental implant treatment in the anterior maxilla - Vladimir S. Todorovic; Mia-Michaela Beetge; Judy Kleyn; Jakobus Hoffman; Andre W. van Zyl (BMC, 2024)
Abstract Background This study used micro-focus X-ray Computed Tomography (micro-XCT) to examine the anatomical differences and dimensions of the maxillary incisive canal (MIC) in a South African population. The accurate imaging yielded dependable results that support earlier research and enhance anterior maxilla surgery planning. Furthermore, these anatomical features are compared between various racial and gender groupings in the study. Methods Using a micro-XCT scanner, 108 human cadaver skulls from the Pretoria Bone Collection were scanned and included in the study. Advanced volume rendering software was employed for measuring the MIC length, diameter, shape, and the buccal bone wall measurements in relation to the MIC. Results Significant anatomical variation in the size and shape of the MIC was identified in the population, with variations seen between racial and gender groups. The incisive foramen (ICO) mean diameter was 6.61 mm, and the MIC length varied from 4.96 to 20.10 mm. There were significant differences in the buccal alveolar bone height between different ethnic groups and gender. Regarding morphological patterns in coronal and sagittal views, single canals were more common in the black population while Y-shaped canals were more common in the white population. The study also introduced a new metric by measuring the mean distances between teeth #11 and #21 and the ICO (1.83 mm and 1.88 mm respectively). Conclusions The complex anatomical differences of the MIC in a South African population were clarified. Clinicians should be aware of tooth sockets in near proximity to the MIC and perform accurate preoperative assessment using sophisticated 3-D imaging and preferable guided implant placement in the anterior maxilla.